Assessment of Mamsa Sara in Pandu Rogi with special reference to Mild to Moderate Anaemia - An Observational Study (AYUSHDHARA, 2024)
Ayurveda is a science of life that offers meaning of health and better living. Assessment of health, disease and assortment of treatment are done mainly by clinical observation by the physician. Sara Pareeksha obliges as a vital diagnostic tool and is one among the method of clinical examination under Dashavidha Atura Pareeksha to evaluate the status of Dhatus. Mamsa Dhatu, provides nourishment to other Dhatus, provide strength, health, happiness and tranquility. Aim and Objective: To evaluate the status of Mamsa Sarata in Pandu Rogi with special reference to mild and moderate anaemia. Materials and Methods: The present study is a cross sectional observational study, conducted in 153 patients of each mild and moderate anaemia categorized based on diagnostic and inclusion criteria. Detailed history taken with a specially designed case proforma and Charakoktha Mamsa Sara Purusha Lakshanas assessed with a validated questionnaire. Result: On analysis of Mamsa Sara Purusha Lakshanas in Pandu Rogi with special reference to mild anaemia and moderate anaemia showed considerable change in the status of above mentioned Sara Purusha Lakshanas within and between two groups of mild anaemia and moderate anaemia. Discussion: In this study, 91.52% and 84.013% of Charakoktha Mamsa Sara Purusha Lakshanas estimated in mild anaemia patients and moderate anaemia patients respectively thus changes in Mamsa Sarata more appreciable in moderate anaemia patients.